Forces Attributed to Dark Matter May Originate from Entangled Particles as Seen in the Shape Of Galaxies Formed by Grbs - Buglyó, Sándor (International Journal of Engineering and Management Sciences, 2018)
Recently, it has been suggested that entangled particles may be connected by a wormhole. If that is right, what is the distance between them we have to take into account when applying Newton’s law of universal gravitation to these particles? We propose the idea that these particles may attract each other regardless of distance, resulting in a force that behaves exactly the same way as the force derived from presumed dark matter. Traces of such a force seem to be present in galaxies due to gamma ray bursts (GRBs) that produce entangled particles which hit various objects. We can observe that in barred spiral galaxies the arms always pass through the nucleus of the galaxy so we believe that the very first GRB happened at the central supermassive black hole (SMBH) and the arms are the traces of this ancient GRB. If we see an unbarred spiral galaxy, we can be certain that the arms do not pass through the core and we think the very first GRB happened close to the core. Ring galaxies may also be considered as a type of spiral galaxies, since there is a section where the ring is broken, i.e. where the arms do not meet. So the very first GRB happened far from the core. Elliptical galaxies may have resulted from an ancient GRB which hit from outside. The arms rotating in opposite directions of the NGC4622 galaxy support our hypothesis. Finally in the silk threads of the spider web of the universe, the traces of GRBs can be seen.